Nutritional Status of Rural Bengalee Girls Aged 10-18 Years of Salboni, Paschim Medinipur, West Bengal, India - De, Kankana; Das, Subal; Bose, Kaushik; Chakraborty, Raja (Asian Journal of Biological and Life Sciences, 2013)
A cross-sectional study of 749 rural adolescent girls of age 10-18 years of Salboni block Paschim Medinipur, West Bengal, India was undertaken to evaluate nutritional status. Anthropometric measurements including weight and height were taken following standard techniques. Body mass index (BMI) was calculated using international BMI cut-off point for children and adolescence from 2 to 18 years of age. Results revealed that girls of 10 years had highest (65.1 %) prevalence of undernutrition. The overall prevalence of undernutrition was (48.3 %). Asignificant age difference existed for weight (F= 41.023, p< 0.001), height (F= 32.907, p< 0.001) and BMI (F= 17.979, p< 0.001). Age difference was also evident (ϰ = 75.214; df= 32; p <0.001) in nutritional status. It was concluded that the studied rural girls of Salboni block were suffering from very high (critical situation) rate of undernutrition. Urgent nutritional intervention programme should be given to them.